Efektifitas Pembelajaran Pada Mata Kuliah Prosa Dengan Pendekatan Project Based Learning Untuk Meningkatkan Hasil Belajar Di Jurusan Bahasa Dan Sastra Inggris - Nasrum (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to determine the process and results of the application of the Project Based Learning (PjBL) learning model in improving learning outcomes in the Prose course in the English Language and Literature Department of UIN Alauddin Makassar. This study uses a Research and Development (R&D) approach with stages simplified into three stages: preliminary study, model development, and model evaluation. Data analysis was carried out at each stage. The results of the study indicate that the application of the PjBL model in learning to write short story texts has a positive impact on the learning activities of students and lecturers. There was an increase in students' writing skills in five assessment aspects: paragraph content, paragraph organization, vocabulary, language use, and mechanics. In phase I, the average student score reached 85 with a sufficient category and 88% completeness. In phase II, there was an increase in the quality of writing skills with an average score of 90 and a good category and the percentage of completeness remained at 88%. These findings indicate that the PjBL model is effective in improving students' short story writing skills, especially through a project-based approach that allows students to be actively and creatively involved in the literature learning process.